Meningkatkan Hasil Belajar dan Berpikir Kritis Siswa Mata Pelajaran Pendidikan Agama Katolik Melalui Model PBL Pada Siswa Kelas II Fase A dalam Materi Bahtera Nuh di SD Xaverius 2 Jambi - Bernadeta Reni Meidi Wijayanti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to determine the increase in cognitive and affective learning outcomes in the dimensions of critical thinking through the PBL model for students at SD Xaverius 2 Jambi. The research is based on the research problem, namely the low level of student learning outcomes in Catholic Religious Education lessons. This type of research is classroom action research with research steps namely planning, implementation, observation and reflection in each cycle. This research consists of two cycles. The research location was at SD Xaverius 2 Jambi for class IIC students with Noah's Ark material. The research was carried out in September 2024. Data collection techniques used learning outcomes tests and affective observation rubrics for critical thinking dimensions. The data analysis technique uses quantitative descriptive techniques. The results of the first cycle of research showed that there were 25 students (74%) who got scores above the KKTP (70%), while there were 9 students (26%) who got scores below the KKTP. The results of the second cycle of research were that students had achieved 100% KKM. This means that if the PBL learning model is implemented well and consistently it will improve student learning outcomes.